Penerapan Framework Flask pada Pembangunan Sistem Informasi Pemasok Barang - Hana Louise Walingkas; Pratyaksa Ocsa Nugraha Saian (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
The supply of goods is one of the important business process in every retail company, to ensure the stocks availability in each store. The slow and inaccurate and errors in the demand and receipt of stocks report are the interrupting factors in the supplying process, thus in this research an information system for supplier was built to make it easier for companies and suppliers in obtaining reports quickly and accurately. In this research, the process and stages of research are carried out sequentially from the system requirements analysis, planning and designing system, implementation, and system testing. The system was built in a web form using Flask framework and Python programming language. In the test conducted by potential users, the tested application received a good response with a percentage of 96.67% users strongly agree that the system can ease the supplying process. Based on the test results, it can be concluded that the information system for supplier built using the Flask framework is able to answer problems that occur in the supplying process